Iron Deficiency Anaemia In Parturients Who Underwent Lower Segment Caesarean Section In Hospital Pulau Pinang - Ling, Ooi Poh; Ibrahim, Noor Airini; Meng Li, Lena Lee; Min Hu, Felicia Su (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Anaemia in pregnancy is a global health problem, especially in less developed countries. Anaemia secondary to iron deficiency in the pregnant population is contributed largely by the physiological haemodilution that occurs during pregnancy and unmet increase in the dietary iron requirements. The aim of this study was to evaluate the prevalence of iron deficiency anaemia (IDA), and its severity in parturients who underwent caesarean section at a tertiary referral hospital. We also aimed to determine contributing factors and effects of IDA on pregnancy outcome for the parturients and their foetuses. Methods: All parturients who underwent LSCS and were found to be anaemic were invited to participate in the survey. Those who consented were recruited to respond to the FACIT – Fatigue scores questionnaire, a validated scoring system used to assess level of fatigability. Antenatal, obstetric, and peri-operative period data were collected in clinical report form. Parturients were asked about their compliance to iron supplementation and reasons of noncompliance. IDA subjects were determined based on anaemic studies done perioperatively. The independent associations between preselected perioperative variables and IDA deficiency anaemia were evaluated. This study was conducted over 6 months, from 1st February 2020 to 31stJuly 2020. Results: 140 anaemic parturients who underwent caesarean section participated in the study. The subjects were ASA I or II, mainly Malay race, aged 25 to 30 years, primigravida, lower to middle-income group, highest education level at secondary school. The prevalence of anaemia in pregnancy was 20.43% while the prevalence of iron deficiency anaemia (IDA) among the anaemic parturients was 64.3%. Patients who complied with iron supplements had a lower IDA percentage (55.1% vs. 90.6%) while those with IDA have a 2.77 higher percentage of low birth weight. Conclusions: The prevalence of anaemia in pregnancy in this study population was 20.43%. The prevalence of IDA in pregnancy is 64.3%, which is lower than the previous published audit in the country. A major contributing factor to IDA in pregnancy is non-compliance to iron supplements. IDA in pregnancy adversely affects maternal and foetal well-being and is associated with low foetal birth weight. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S22